STUDY OF PROPERTIES OF COATINGS FORMED BY METHODS OF PLASMA, GAS FLAME AND ELECTRIC ARC SPRAYING - Духота, Олександр; Кіндрачук, Мирослав; Харченко, Володимир; Науменко, Ніла (Problems of Friction and Wear, 2022)
Among the existing and actively developing methods of engineering of wear-resistant surfaces, one of the most universal and productive are the methods of gas-thermal coating (GTS). At present, a wide range of materials, both simple and complex in terms of content, has been developed and used for GTS, which allows to obtain coatings with a variety of properties. However, the recommendations for their use in most cases indicate only the functional purpose of the coating without taking into account the full range of requirements for performance properties, which are set by the operating conditions of the part. Research on establishing the relationship between the initial composition of the material, technological parameters of spraying and tribotechnical properties of coatings will help to increase the efficiency and wider introduction of GTS technologies to solve tribotechnical problems. The results of experimental studies of wear patterns in the conditions of fretting-corrosion of a number of coatings formed by the methods of plasma, pulse-plasma and high-speed gas-flame spraying are presented. Peculiarities of formation in the process of spraying of structural-phase composition of coatings and its influence on their wear resistance are analyzed. Analytical studies of the regularities of stress-strain formation in the system "gas-thermally sprayed coating-base" and studies to evaluate the effectiveness of various technological influences and methods of designing coatings for wear resistance and fatigue life of parts with gas-thermally sprayed coating. Studies have shown the high efficiency of antifriction and antiwear properties of the lubricant on the surface of the molybdenum coating, which is due to its high (due to porosity) oil retention capacity and resistance to destruction of the marginal lubricating layers.